The PHENOMENA OF MUKBANG IN THE PERSPECTIVE OF HADITH: FENOMENA MUKBANG DALAM PERSPEKTIF HADIST - Maysa Latifa; Firani Putri; Charles Charles (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2023)
Technological advances in the current Millennial era and various kinds of phenomena that can affect people's behavior. One of them is Mukbang which is seen as incompatible with eating habits based on Islamic religious guidance. This study aims to examine Mukbang from a perspective or point of view in Islamic religious teachings, especially from hadith perspective. With a research methodology, namely the study of literature by examining through books and journals related to eating habits in Islam. In the mukbang phenomenon, there are many things that are not in accordance with eating habits from the point of view of Islamic teachings, such as eating excessive portions, eating with your left hand or eating without reading a prayer first. The conclusion of the research examines that Mukbang is not a good show to be used as a spectacle in terms of education because it teaches little about Morals, especially in the Adab of eating in Islamic religious teachings.